Rancang Bangun Sistem Informasi Pengolahan Data Lapangan Futsal GOR Mampis Rungan Berbasis Web - Ryan Adi Saputra; Wilia Ismiyarti (Bulletin of Information Technology (BIT), 2022)
This study aims to design an information system for processing futsal field data GOR Mampis Rungan. The system development method is carried out through an extreme programing approach. This approach is carried out using 4 stages, namely planing, design, coding, testing. The design stage is carried out using UML tools using four diagrams, namely usecase diagrams, activity diagrams, sequence diagrams, and class diagrams. The interface design stage is to use Balsamiq. The last stage is to build a system, this stage is carried out using PHP and MariaDB languages. This research succeeded in designing and building an information system for processing futsal field data GOR Mampis Rungan, has been tested using the blackbox method. The benefit of this application is that it makes it easier for GOR daily administrators to process data and makes it easier for customers to order the field online